PEREMPUAN DALAM PERSPEKTIF POLITIK, HUKUM, DAN HAM (KAJIAN TERHADAP NOVEL-NOVEL INDONESIA MUTAKHIR KARYA WANITA PENGARANG) - - Sulaiman (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2011)
Literature, among society, cannot be separated from the society itself. Literature lives because there is a society, a writer or an author who creates the work. In addition, literature lives from the soul of the society, meaning that the society is the object of its story. In this case, Faruk (1999: vi) clarifies that talking about literary work actually cannot be separated from society. It means that the presence of literary work is asreflection of the existence of society. It also can become the conscience of the authors by looking at the reality around them, whether from self-experience or the result of telescopic research about the attitudes of the surrounding society.